Effectiveness of the Public Relations Role of the Palu Pratama Tax Service Office (KPP) in Increasing Public Awareness of Paying Taxes - Risal, Risal; Sukmawati, Sukmawati; Hasdin, Hasdin; Kulyawan, Roy; Makmur, Windy; Nasran, Nasran (AURELIA: Jurnal Penelitian dan Pengabdian Masyarakat Indonesia, 2025)
The aim of this research is to describe the strategy of the Public Relations Role of the Palu Pratama Tax Service Office (KPP) in increasing public awareness of paying taxes. To describe the effectiveness of the Public Relations Role of the Palu Pratama Tax Service Office (KPP) in increasing public awareness of paying taxes. This type of research is descriptive qualitative, the subjects of this research are seven people consisting of two public relations officers in the executive service section, five taxpayers from the general public. The research method for collecting data is through observation, interviews and documentation. The analysis was carried out using 3 stages, namely data reduction, data presentation, and conclusions. The results of the research show that the strategies carried out by the Public Relations of the Pratama Palu Tax Service Office (KPP) in increasing public awareness of paying taxes are: 1) Operational strategy, carried out by the public relations of the Pratama Palu KPP, namely tax corners in four strategic locations in the city of Palu. 2.) Persuasive and educational strategy, namely the use of the sipabeta application to make it easier to manage property taxes. 3.) Collaboration strategy, KPP Pratama Palu public relations collaborates with the Regional Financial and Asset Processing Agency (BPKAD) of Palu city in socializing taxation. The effectiveness of the public relations role of KPP Pratama Palu in increasing public awareness of paying taxes: 1) As a communicator, conducting outreach with the public about the importance of paying taxes. 2) as an image maker, socialize the sipabeta system to make it easier for people to pay property taxes. 3) as a Conceptor, conveying information and educational activities to the community. 4) As a Problem Solver, plays a role in resolving problems in public communication, tax service complaints.